PERAN KUALITAS LAYANAN DALAM MEMEDIASI HUBUNGAN ANTARA KARYAWAN BERORIENTASI PELANGGAN DENGAN KEPUASAN PELANGGAN DI BULGARI RESORT BALI - Purbawisesa, Niky; Wardana, I Made; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.11.TAHUN 2018, 2018)
This study aims to explain the role of service quality in mediating customer-oriented employees with customer satisfaction at Bulgari Resort Bali. This research was conducted in Bulgari resort with the customer population who had stayed at least once in Bulgari Resort Bali from January to July 2016. Questionnaires were distributed to 130 respondents by purposive sampling method. This study uses a variance based or component-based approach of PLS ??(Partial Least Square) analysis technique. The results of this study indicate that customer-oriented employees have a positive and significant impact on customer satisfaction as well as on service quality. Quality of service is also found to have a positive and significant effect on customer satisfaction. Furthermore, service quality is proven to mediate partially the impact of customer-oriented employees on customer satisfaction. The implications of this study indicate that customer-oriented service quality and employee play an important role in customer satisfaction, this can be the basis for the perpetrators of the hospitality industry in general and the management of Bulgari resort Bali in particular to improve the quality of customer service and employees oriented. Thus it is suggested that the management can implement an integrated and sustainable training program in order to be able to provide satisfaction for customers.